Geometallurgy and data analysis. Importance and applications in Peru - Castro Andrade, Julio Alejandro (2022)
Geometallurgy is defined as the study of the genesis of minerals with respect to the performance of their metallurgical processing. The construction of geometallurgical models is of the utmost importance for the technical-economic evaluation of the deposit. The robustness of the model depends on the number of resources invested to generate potential information that will serve in decision making. The relevance of the geometallurgical model has a high value in mining management, which serves as an instrument for the planning, exploitation and design of metallurgical processes according to the type of deposit. Using the information to maximize economic performance in concentration processes has enormous potential and challenge for plant operators. This article will discuss the use of data analysis and its applications in several successful cases for porphyry-type deposits, taking into account the use of traditional statistical methods and supervised classification algorithms.